Application of Metathesis Protocols to the Stereocontrolled Synthesis of Some Functionalized β-Amino Esters and Azaheterocycles - Semghouli Anas (CHEMICAL RECORD, 2023)
In this account our aim was to give an insight into the application of metathesis protocols (ROM, RCM, RCEYM, CM, RRM) for the synthesis of various azaheterocyclic frameworks. Due to the high biological potential and importance in peptide chemistry and drug design of beta-amino acids our intention is to give a highlight on the synthetic procedures and transformation of these class of compounds with the above-mentioned metathesis strategies with emphasis on selectivity, stereocontrol, substrate-directing effect or functional group tolerance.